Impact of Time of Surgery on the Outcome after Surgical Stabilization of Rib Fractures in Severely Injured Patients with Severe Chest Trauma—A Matched-Pairs Analysis of the German Trauma Registry - Becker, L.; Schulz-Drost, S.; Spering, C.; Franke, A.; Dudda, M.; Kamp, O.; Lefering, R.; Matthes, G.; Bieler, D.; , on behalf of the Committee on Emergency Medicine, Intensive Care; Trauma Management (Sektion NIS) of the German Trauma Society (DGU) (Frontiers in Surgery, 2022)
Purpose In severely injured patients with multiple rib fractures, the beneficial effect of surgical stabilization is still unknown. The existing literature shows divergent results, and the indication and especially the right timing of an operation are the subject of a broad discussion. The aim of this study was to determine the influence of the time point of surgical stabilization of rib fractures (SSRF) on the outcome in a multicenter database with special regard to the duration of ventilation, intensive care, and overall hospital stay. Methods Data from the TraumaRegister DGU collected between 2010 and 2019 were used to evaluate patients above 16 years of age with severe rib fractures [Abbreviated Injury Score (AIS) ≥ 3] who received an SSRF in a matched-pairs analysis. In this matched-pairs analysis, we compared the effects of an early SSRF within 48 h after initial trauma vs. late SSRF 3–10 days after trauma. Results After the selection process, we were able to find 142 matched pairs for further evaluation. Early SSRF was associated with a significantly shorter length of stay in the intensive care unit (16.2 days vs. 12.7 days, p = 0.020), and the overall hospital stay (28.5 days vs. 23.4 days, p = 0.005) was significantly longer in the group with late SSRF. Concerning the days on mechanical ventilation, we were able to demonstrate a trend for an approximately 1.5 day shorter ventilation time for patients after early SSRF, although this difference was not statistically significant (p = 0.226). Conclusions We were able to determine the significant beneficial effects of early SSRF resulting in a shorter intensive care unit stay and a shorter length of stay in hospital and additionally a trend to a shorter time on mechanical ventilation.